Olacaceae endémicas del Perú - León, Blanca (2006)
The Olacaceae are represented in Peru by nine genera and 23 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly trees and shrubs. Here we recognize one endemic species in the genus Aptandra. This species grows in Humid Lowland Amazonian Forests region, between 100 and 150 m elevation. It has not been recorded in the Peruvian System of Protected Natural Areas.